Juridical Analysis Contained With Civil Processors Manipulating Electronic Information Data In The Pre-Work Card Registration Project (Analysis Of The Medan District Court Decision With Case Number 542/pid.sus/2022/pn mdn) - Sony Prayudha Winata; Andry Syafrizal Tanjung; Sumarno, Sumarno (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Information technology is now a two-eyed sword because, in addition to contributing to the advancement of human well-being, progress, and civilization, it is also an effective means of committing acts against the law. A new legal regime known as cyber law or telematics law has emerged in recent times. Cyber law is internationally used for legal terms related to the use of information and communication technology. Similarly, telematic law is an embodiment of the convergence of telecommunications law, media law, and computer law. Speaking of crime in information technology is not out of the rules governing the crime, then it was the basis of the birth of the Act No. 11 of 2008 on Electronic Information and Transactions and now amended to the Law No. 1 of 2024 on Amendment of the Law No. 11 of 2008 on Information and Electronic Transaction. The criminal offense of falsification of documents through the Internet belongs to the category of cybercrime, which can be committed by both individuals and organizations. Cybercrime is a term that refers to criminal activity, with a computer or computer network being the tool, target, or place of crime. Electronic Information Manipulation Crimes themselves are a frequent occurrence in Indonesia. There are many court rulings that judge electronic information manipulation crimes; one of them is the ruling of the Medan State Court with registration number 542/Pid.Sus/2022/PN Mdn, where the accused is named Angga Risnawan. The date of birth of the accused is 22 years of private employment. The accused was found guilty of committing “those who committed, ordered, and accompanied acts intentionally and without the right or against the law of manipulating, creating, altering, eroding, or corrupting electronic information and/or electronic documents with the aim of making the electronic information and/or electronic document considered authentic data